SELF-EFFICACY AND MOTIVATION AS CORRELATES OF SECONDARY SCHOOL STUDENTS’ACADEMIC ACHIEVEMENT IN PHYSICS (UNIZIK Journal of STM Education, 2021)
The study was carried out on Self-efficacy and Motivation as correlates of secondary school students’ academic achievement in Physics in Enugu state.. Three research questions and three null hypotheses were used to guide the study. The researchers adopted a correlation survey design. The sample comprises of 384 SSII physics students which were drawn from 12 out of 25 government owned secondary schools in Enugu Education Zone of Enugu State using a multi-stage sampling technique. Physics Self- Efficacy Questionnaire (PSEQ) and Physics Motivation Questionnaire (PMQ) were used for data collection. The PSEQ consists of 20 items measured in 5-point Likert scale format and adapted from Sawtelle (2011) while the PMQ also consists of 20 items measured in 5-point Likert scale format and adapted from Mubeen and Reid (2014). Pearson Product Moment Correlation and Regression analysis were used to answer and test the research questions and hypotheses respectively. The findings of the study indicated that self-efficacy was not a significant factor on students’ academic achievement in physics, while motivation was a significant factor on students’ academic achievement in physics. The findings also revealed that there was a low positive relationship between self-efficacy and motivation on students’ academic achievement in Physics. Motivation was of great influence on students’ academic achievement in Physics while self-efficacy had no significant influence on academic achievement in Physics. Based on the findings, it was recommended that; Teacher education programmes should train teachers on ways to improve their students’ motivation, both state and federal governments should organize workshops and seminars and sponsor teachers to attend in-service courses on how to improve their teaching skills in order to enhance their students’ achievement.
Keywords: Self-efficacy; motivation; academic achievement